EFEKTIVITAS PROGRAM GERAKAN SUMSEL MANDIRI PANGAN DALAM MENCAPAI KESEJAHTERAAN MASYARAKAT DESA LUBUK BATANG BARU KECAMATAN LUBUK BATANG KABUPATEN OGAN KOMERING ULU - Nabila Aisyah; Aprilia Lestari; Marratu Fahri (Jurnal Ilmu Pemerintahan, 2025)
The South Sumatra Independent Food Movement Program was a program launched by the provincial government to improve the welfare of people from cities to villages. The research was carried out from March to April 2024. Based on the results of the research, the effectiveness of the South Sumatra Mandiri Pangan Movement Program in Lubuk Batang Baru village could be seen from 4 indicators 1) Accuracy of program targets, indicating that the accuracy of targets for distribution of aid in the South Sumatra Mandiri Pangan Movement Program had been achieved. effective. 2) Program socialization, socialization that had been carried out by the village government has been implemented optimally because there are extension workers in every sub-district in OKU Regency. 3) Program Objectives: The Government of Lubuk Batang Baru Village, Lubuk Batang District, Ogan Komering Ulu Regency, in implementing the South Sumatra Independent Food Movement Program has been quite effective, because the results obtained from this program were in accordance with the initial objectives that have been set, although there were still things that are not yet clear. maximum was reached. 4) Program monitoring, that the assessment of the effectiveness of the South Sumatra Independent Food Movement Program is seen from the program monitoring indicators that it was effective. Because there was maximum effort made by the village government in collaboration with Agricultural Extension Officers in monitoring the South Sumatra Independent Food Movement Program, namely by empowering extension officers in each sub-district and also seed distribution staff who go directly to the field to check the implementation of the program. Program activities and monitoring have been carried out effectively but must be optimized, especially the speed of response from the extension team and the village government regarding the obstacles experienced by aid recipients.